THE FUNCTIONS OF DERIVATIONAL SUFFIXES IN INSPIRATIONAL BOOK WRITTEN BY MARIA AND ELIZABETH RAHAJENG “BECOMING UNSTOPPABLE” - Putri, I Dewa Ayu Agung Bintang Maharani (Journal of English Teaching, Applied Linguistics and Literatures (JETALL), 2023)
This study focuses on the derivational suffixes found in Maria and Elizabeth Rahajeng's book "Becoming Unstoppable." The study encourages further exploration and understanding of derivational suffixes, by comprehending what is the function derivational suffixes, individuals can enhance the language skills and improve communication. The study identifies and explains the derivational suffixes using the theories proposed by (Lieber, 2009) and(Carstairs-Mccarthy, 2002), shedding light on the process involved. Both formal and informal methods were used to describe the study's findings. The writer identified three forms of derivational suffix functions: category-changing lexeme formation, meaning-changing lexeme formation, and both category and meaning-changing lexeme creation. The process of derivational suffixes was described using labeling and bracketing. From the outcome, a total of 159 data were identified, with the main type function being category-changing lexeme formation 129 data, followed by both category-meaning changing formation 30 data. However, meaning-changing lexemes were not found in the data source. This study underscores the significance of morphological terms in language, as they facilitate the creation of new words from diverse languages and word forms.